Oculopharyngeal involvement in familial neurogenic muscular atrophy. Issue 1 (February 1973) - Matsunaga, M.; Inokuchi, T.; Ohnishi, A.; Kuroiwa, Y.
Abstract : A Japanese family with progressive spinal muscular atrophy is presented. Seven members in two generations were affected and the mode of inheritance was probably an autosomal recessive trait. A characteristic feature of this family was the presence of oculopharyngeal involvement in some of the affected members, in addition to the variable distribution of muscular atrophy among each of the affected members, such as mainly proximal or distal atrophies in the limbs. In one case the oculopharyngeal weakness appeared without limb involvement. The changes in the extremities were thought to be of neurogenic origin, and so was the progressive external ophthalmoplegia seen characteristically in these cases, although the latter was similar to ocular myopathy.